Critical Analysis of Public Health Preparedness and Multisector Collaboration in Crisis Management - Alismail, Abdullah Mujahid Abdullah; Aboun, Moraya Mubark Ali; Al yami, Mohsen Hussein Ali; Al Rashah, Ahmad Saleh R; Mashahhim, Ibrahim Hussain Ali; Alyami, Saleh Mobark; Alsalamah, Salem Fahad Mohammed; Alsalamah, Mohammed Fahad Mohammed; Abdli, Abdullah Hussain; ALRashah, Rashed Fahad Rashed (Journal of Ecohumanism, 2024)
It has become clear that preparedness and management of crises have also become important issues regarding natural disasters, epidemics, and other related calamities. This review systematically examines the existing approaches and models to prepare public health collaboratively, with special attention to intersectoral integration. Intense cooperation between representatives of the governmental and non-governmental levels, healthcare institutions, and the private sector is the key to success in crisis management. The present review enlists examples regarding recent outbreaks, such as cases, assets, liabilities, and opportunities for reflection. The purpose will be to reveal the best practices that would help improve public health systems’ abilities to address future challenges through the lens of multisector collaboration and preparedness framework development.